Financial development-economic growth nexus: a bibliometric analysis - Madya Gan Pei Tha, Awadh Ahmed Mohammed Gamal, Norimah binti Rambeli @ Ramli (Tanjung Malim, 2024)
Financial development-economic growth nexus: a bibliometric analysis by Madya Gan Pei Tha, Awadh Ahmed Mohammed Gamal, Norimah binti Rambeli @ Ramli